Change of indicators rheography at the qualified athletes-swimmers when overcoming a marathon distance - Синюгіна [Mariya Sinyugina] Марія Борисівна (Slobozhanskyi Herald of Science and Sport, 2013)
In work dynamics of changes of indicators of the central blood circulation at athletes-swimmers of different qualification is considered during a marathon distance (10000 m). The carried-out analysis of indicators rheography of athletes-swimmers during overcoming of a marathon distance allowed to define changes of indicators of the central blood circulation on separate sites of a distance. During research dependence of changes of indicators rheography of swimmers on their sports qualification is proved. It is established that more optimized work of cardiovascular system for performance of heavy marathon loadings at swimmers high sports category, least – at athletes of the low sports category.